(untitled) (Research, Society and Development, 2020)
In this case study, we tried, initially, to understand how the State School of Professional Education (EEEP) Professor Lysia Pimentel Gomes Sampaio Sales, considered a reference educational institution for its academic results, has managed to develop its pedagogical actions in the context of remote education. However, with the evolution of our studies and observations, we need to make a methodological approach to analyze, specifically, how the curricular integration between common base and technical base occurs in the Mechanical Manufacturing course offered by the teaching unit. This cut was necessary because we were unable, in an article, to contemplate in an analytical way all the pedagogical processes that the school has been developing in this period of pandemic. In order to support our analysis, we used the authors Acácia Kuenzer and Jurjo Torres Santomé as a theoretical reference to mean the terms interdisciplinarity and curricular integration, since they support the conception of the school itself, as mentioned in the Pedagogical Political Project-PPP(2019). It was possible to conclude, in these three months of immersion in the school universe, that the teachers’ posture is decisive to build teaching alternatives that allow integration of theory and practice, guaranteeing the emancipation of the subject.